PENINGKATAN KEMAMPUAN MEMAHAMI CERITA DALAM BUKU PELAJARAN BAHASA INDONESIA MELALUI METODE ROLLING BOOK PADA SISWA KELAS V SEKOLAH DASAR NEGERI 64 TO’BULUNG KOTA PALOPO - Nur Andini (Institut Agama Islam Negeri Palopo, 2019)
The focus of the problem in this research is the application of the method of word guessing and improvement of science learning outcomes in the human digestive organ material in grade V Madrasah Ibtidaiyah 43 Batulotong. Furthermore, this study aims to improve students' understanding in teaching subjects IPA Madrasah Ibtidaiyah 43 Batulotong so that the quality of learning can be achieved optimally. This research uses qualitative approach and quantitative approach with Classroom Action Research (CAR) which is designed through three cycles. The research data obtained were analyzed by using descriptive statistic formula (percentage) to express descriptively the research result. Furthermore, to discuss and explain the results of research that is qualitative descriptive techniques used data reduction analysis, data presentation, and conclusion. From the research results showed that in the pre cycle stage, the average value of student learning outcomes is 50.70. With a classical thoroughness of 7.69%. After implemented by applying the method of guessing words, in the first cycle, the average score of student learning outcomes is 63.92 with 39% complete classical learning. Furthermore, in cycle II with the average value of student learning outcomes is 88.62 with 79.16% classical learning completeness. Then, continued in cycle III with the average value of student learning outcomes is 90.42 with classical learning completeness 88.46%. Thus, students' learning outcomes on science lessons in grade V Madrasah Ibtidaiyah by applying the word guess method can increase in each cycle. Therefore, the method of word guessing should be used as a reference by teachers in science learning activities in SD / MI, especially in Madrasah Ibtidaiyah 43 Batulotong.